Design of Net-learning Systems Based on Experiential Learning - Pimentel, Juan R. (Online Learning, 1999)
The theory of experiential learning is briefly reviewed and a model of the learning process is presented. The paper then discusses and characterizes a virtual learning environment and its relationship to experiential learning and learning styles. An approach for designing virtual learning environments is presented taking into account the technology for learning. A prototype for a virtual learning environment designed and built by the author and known as LeProf is then discussed along with its application in the design of an educational site for learning electrical circuits.